2011
DOI: 10.1089/ast.2010.0530
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Nucleobases from Formamide in the Presence of Iron Oxides: Implication in Chemical Evolution and Origin of Life

Abstract: Simple compounds like HCN, which have one C and one N, are proposed as the probable precursors for biomonomers. Formamide, a hydrolysis product of HCN, is known as the precursor of various biologically important compounds, for example, nucleobases (purines and pyrimidines). In this paper, we report our results on the synthesis of nucleobases, adenine, cytosine, purine, 9-(hydroxyacetyl) purine, and 4(3H)-pyrimidinone from formamide, using iron oxide (hematite) and oxide hydroxides (goethite and akaganeite) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…Hematite and akaganeite appear as rod shaped structures, 102.16, 85.93 nm long and 18.32, 18.07 nm thick, respectively. The occurrence of chloride peak confirms the formation of akaganeite (Shanker et al, 2011).…”
Section: Characteristics Of Iron Oxidessupporting
confidence: 53%
“…Hematite and akaganeite appear as rod shaped structures, 102.16, 85.93 nm long and 18.32, 18.07 nm thick, respectively. The occurrence of chloride peak confirms the formation of akaganeite (Shanker et al, 2011).…”
Section: Characteristics Of Iron Oxidessupporting
confidence: 53%
“…Some of the most successful attempts to simulate primitive abiogenic reactions have been conducted under conditions that are compatible with reconstructed conditions at the geothermal fields of the anoxic Earth. These promising experiments include syntheses of biologically relevant compounds in formamide solutions (98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(111)(112)(113)(114)(115), photosynthesis/photoselection of natural nucleotides (120)(121)(122)133), montmorillonite-catalyzed formation of long RNA oligomers (118) and membrane vesicles (134), RNA polymerization in the eutectic phase in water-ice (135), abiotic UV photosynthesis of the tricarboxylic acid cycle intermediates at ZnS (83,84) and TiO 2 crystals (136), as well as UV-triggered recharging of ADP to ATP (137). Further experimental exploration of models that mimic the conditions at anoxic geothermal fields are expected to shed more light on precellular evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been shown that silica minerals catalyze the formation of adenine and cytosine from formamide (103,111) and that TiO 2 , the main component of the mineral rutile, could catalyze the formation not only of purine derivatives but also of thymine, 5-hydroxymethyluracil, and even acyclonucleosides (112). Even widespread iron oxides have been shown to catalyze the synthesis of nucleobases from formamide (113). d) Spontaneous polymerization events, which are thermodynamically unfavorable in the bulk water, would be favored at geothermal fields.…”
Section: Terrestrial Anoxic Geothermal Fields As Cradles For Earliestmentioning
confidence: 99%
“…5,6 Because the one-pot synthesis from FM can give both purines and pyrimidines, 7, [12][13][14][15][16][17][18][19][20][21][22] it is reasonable to expect that a free radical route also leads to pyrimidines. In this context, we set out to perform quantum chemical computations to investigate the generation of nucleobases such as cytosine, uracil and thymine from FM, and the small species which were present in the prebiotic atmospheres (in particular of Titan) such as HCN,…”
Section: Introductionmentioning
confidence: 99%